INNOVATIVE METHODS OF TEACHING HISTORY AT MODERN UNIVERSITIES - A. Yu. Suslov; M. V. Salimgareev; Sh. S. Khammatov (Образование и наука)
Introduction. As a discipline, History holds a specific place among disciplines of a humanitarian cycle of educational programs of higher education institutions regardless of university specialities. History plays an important role in the course of formation of a citizen and development of critical thinking of a personality as an element of a common culture. However, new federal standards require a drastic reduction of the classroom hours for studying a History course by students of non-humanitarian specialties, and, at the same time, enhancement of the contents of a discipline (its reorientation from History of Russia towards World History). Therefore, History programmes and courses demand up-to-date approaches, methods and didactic means to provide formation of holistic worldview of future experts.The aim of the article is to consider the features of innovative methods application in teaching history in high school taking into consideration modernization processes.Methodology and research methods. The research undertaken is based on activity and competence-based approaches. The methods of analysis and synthesis of the academic literature on the research topic were used; the methods of reflection and generalization of teaching activities of the Department of Humanitarian Disciplines of theKazanNationalResearchTechnologicalUniversity were applied as well.Results and scientific novelty. A modern view on historical education has been proposed as means of students’ systems thinking formation, designing the ideas about the world historical process among students, the mission ofRussia in this process, and evolution ofRussia as a part of the modern civilization. It is stated that History university course is designed not only to give the students strong subject knowledge, but also to create axiological orientations and abilities on the basis of the analysis of historical collisions, objective and subjective factors of society development. Moreover, modern university History course teaches students to establish casual links, to defend own position with deep arguments, to reproduce and present information streams. Learning activities presented above will definitely help future experts to become competent professionals. Learning objectives can be solved by means of a complex of the following innovative pedagogical technologies: problem-based, design and game methods that stimulate cogitative activity of students; dialogue (interactive) forms of training (case-study, debate, discussion) that promote mutual understanding between a teacher and a student, joint solution of educational tasks, and acquisition of positive communicative skills among students. The case study of new formats of History studying is described; it is shown that introduction of new formats into educational practice is possible only under the conditions when a teacher masters the ways of organization and conducting discussions, develops an understanding of distance education and virtual training environments. Students, for their part, have to demonstrate high motivation and activity, to find independently required data, to process and analyze information including historical original sources.Practical significance. Guidelines for application of interactive methods of teaching history in non-humanitarian universities are provided; recommendations for the organization of independent work of students are given as well. The recom mendations have universal character and can be used by teachers of other disciplines after applying specific content adaptation.